2022
DOI: 10.4178/epih.e2022069
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of colonization by extended-spectrum beta-lactamase-producing Gram-negative bacilli in hemodialysis patients and their household contacts in Colombia: dissemination between the community and the hospital

Abstract: High frequency of colonization by extended-spectrum beta-lactamase-producing Gram-negative bacilli in hemodialysis patients and their household contacts: dissemination between the community and the hospital AbstractObjectives: Increase in colonization by beta-lactam-resistant Gram-negative bacilli (BR-GNB) represent a risk for infections and bacterial resistance spread, not only in hospitals but community. Hemodialysis patients and their household contacts transit constantly between the two environments. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Among the microorganisms identified, an acquired resistance profile was found in 63% of the isolates, in agreement with recent studies that have shown a gradual increase in antimicrobial resistance; among the proposed mechanisms, selective pressure due to inadequate use of antibiotics has been considered [ 22 , 25 ]. In South Korea, Nham et al found a relationship between the development of BLEE-producing K. pneumoniae and the previous use of antimicrobials [ 20 ], without ruling out cross-bacterial transmission in different institutions, especially in those with low antimicrobial use, and the introduction of resistant bacteria from the community [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the microorganisms identified, an acquired resistance profile was found in 63% of the isolates, in agreement with recent studies that have shown a gradual increase in antimicrobial resistance; among the proposed mechanisms, selective pressure due to inadequate use of antibiotics has been considered [ 22 , 25 ]. In South Korea, Nham et al found a relationship between the development of BLEE-producing K. pneumoniae and the previous use of antimicrobials [ 20 ], without ruling out cross-bacterial transmission in different institutions, especially in those with low antimicrobial use, and the introduction of resistant bacteria from the community [ 26 ].…”
Section: Discussionmentioning
confidence: 99%